Lead Concentration in The Soil Around a Used Battery Recycling Site in Tangerang Regency, Indonesia - Fauzi, Ridwan; Hidayat, Muhamad Yusup; Hindratmo, Bambang; Masitoh, Siti; Saragih, Grace Serepina (UI Scholars Hub, 2021)
Long-term lead (Pb) exposure can affect human health. Used battery recycling is a source of Pb emission, and the smoke from the facility carries Pb particles that accumulate in the soil. This study aimed to determine the concentration of accumulated Pb in the soil around Kadu Manis Battery Recycling Industrial Estate, Tangerang Regency, Banten Province, Indonesia in 2018. Soil samples were collected by employing a purposive strategy in four directions from the hot spot at a 0–7.5 km radius. Pb content in the soil was analyzed using a modified version of the official method from American Public Health Association number 3030-H in 2012 and work instructions for metal 01 in 2014. Results showed that the Pb concentration in the soil around this site was below the threshold with an average value of 94.43 mg/kg dry weight and a range of 16.56–279.42 mg/kg dry weight. The soil closest to the facility had the highest Pb concentration. These findings indicated that the management of emission from used battery recycling site must be improved.